Dampak Penerapan Nilai-Nilai Moral melalui Pembelajaran Fikih tentang Hudud pada Siswa Kelas XI - Laila Mauludiyah; Sofiah (Universitas Pakuan, 2026)
THE IMPACT OF THE APPLICATION OF MORAL VALUES THROUGH FIQH LEARNING ABOUT HUDUD ON GRADE XI STUDENTS This study aims to describe the implementation of moral values in fiqh learning on the topic of hudud and to analyze its influence on students’ understanding, attitudes, and behavior. The study is grounded in the importance of Islamic Religious Education as a medium for character formation, especially amid various moral challenges faced by adolescents. Fiqh learning, which has often been oriented toward cognitive mastery, needs to be directed toward strengthening moral values so that the material is not only understood theoretically but also internalized and applied in daily life. This research employed a qualitative approach with a field research design. Data were collected through observation, interviews, and documentation, and were analyzed through data reduction, data display, and conclusion drawing. The findings indicate that the integration of moral values in fiqh learning on hudud can improve students’ understanding in cognitive, affective, and behavioral domains. Students demonstrated positive changes, including increased honesty, responsibility, discipline, and awareness of obeying rules. The internalization of values occurred through contextual learning, teacher role modeling, and habituation during the learning process. Therefore, moral value-based fiqh learning plays an important role in shaping students’ character and should be continuously developed so that Islamic Religious Education functions not only as a process of knowledge transfer but also as a means of fostering students’ moral conduct.